PENGARUH PENGUNGKAPAN ISLAMIC SOCIAL REPORTING, CORPORATE SOCIAL RESPONSIBILITY DAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN BANK UMUM SYARIAH - Shofiyatun, Yeni; Fakhruddin, Iwan; Hariyanto, Eko; Hapsari, Ira (JURNAL ILMIAH EDUNOMIKA, 2024)
The aim of this research was to analyze the influence of disclosure of Islamic Social Reporting (ISR), Corporate Social Responsibility (CSR), Independent Board of Commissioners (DKI) and Sharia Supervisory Board (DPS) on Financial Performance in Sharia Commercial Banks. This type of research is quantitative research. The population in this research is Sharia Commercial Banks in Indonesia which are registered with the Financial Services Authority (OJK) from the 2018-2022 period. The number of samples used were 66 data of 15 bank in Indonesia. The sampling technique used was purposive sampling. The data collection method is observation through data analysis techniques using E-views 12. The results of this study show that (1) Islamic Social Reporting (ISR) has no effect on financial performance, (2) Corporate Social Responsibility (CSR) has an effect positively on the financial performance, (3) the Board of Independent Commissioners (DKI) has a positive influence on the financial performance, (4) the Sharia Supervisory Board (DPS ) has no effect on the financial performance.